Gath and the Structure of the “Philistine” Society - Kassis, Hanna E.
265-266 zu Dagan; 267 Vergleiche mit anderen Invasoren im Vorderen Orient “culturally subsumed by the conquered society”: Hyksos, Mitanni, Sam’al.